ASSESSMENT AND IDENTIFICATION OF SOME NOVEL NOX REDUCING REAGENTS FOR SNCR PROCESS - Mahmood, A.; Javed, M. T.; Irfan, N.; Hamid, A.; Waheed, K. (The Nucleus, 2020)
Nitrogen oxides (NOx) are one of the most hazardous air pollutants arising from the combustion processes. Because of the implementation of strict emission limits many NOx removal technologies have been developed. In the present work post combustion NOx removal technique that is Selective Non-Catalytic Reduction (SNCR) has been investigated in a pilot scale 150 kW combustion rig facility. Investigation has been performed using some novel NOx reducing reagents like urea, ammonium carbonate and mixture of their 50%-50% aqueous solution within the temperature range of 700 to 1200 o C, at 1.1% excess oxygen and background NOx level of 500 ppm. The effects of these reagents were determined in term of their temperature characteristics and molar ratio. Among the reducing reagents used urea solution gave the highest NOx removal efficiency (81%) and was attractive due to its superior high temperature (1000 to 1150 o C) performance, ammonium carbonate was more effective at lower temperature range (850 to 950 o C) though its efficiency (32%) was lower than urea, while 50-50% solution of urea and ammonium carbonate gave higher efficiency than ammonium carbonate but slightly lesser than urea within a wide temperature range (875 to 1125 o C). It was also observed that the NOx removal efficiency was increased with increasing the molar ratio.